Stereoselective Synthesis of d4-(S)-Lysine from (S)-Serine - Kohr, Michael; Kazmaier, Uli (Synthesis, 2018)
Tetradeuterated (S)-lysine can easily be obtained from protected (S)-serine in a few steps including a Cu-mediated cross coupling and subsequent platinum-catalysed deuteration.
Keywords: amino acids; copper; cross coupling; deuteration; isotope labelling; lysine